Knowledge Gaps and Emerging Research Areas in Intrauterine Growth Restriction-Associated Brain Injury - Fleiss, Bobbi; Wong, Flora; Brownfoot, Fiona; Shearer, Isabelle K.; Baud, Olivier; Walker, David W.; Gressens, Pierre; Tolcos, Mary (Frontiers in Endocrinology, 2019)
Intrauterine growth restriction (IUGR) is a complex global healthcare issue. Concerted research and clinical efforts have improved our knowledge of the neurodevelopmental sequelae of IUGR which has raised the profile of this complex problem. Nevertheless, there is still a lack of therapies to prevent the substantial rates of fetal demise or the constellation of permanent neurological deficits due to IUGR. The purpose of this article is to highlight the gaps in our clinical and translational knowledge and available tools that are hampering our collective efforts to improve the neurological outcomes of those diagnosed with IUGR. Also, we will focus on cutting-edge tools and techniques that can provide novel insights into this disorder and technologies that offer the potential for better drug design and delivery. We will cover topics including: how we can improve our use of crib-side monitoring options, what we still need to know about inflammation in IUGR, the necessity for more human post-mortem studies, lessons from improved integrated histology-imaging analyses regarding the cell-specific nature of magnetic resonance imaging (MRI) signals, options to improve risk stratification with genomic analysis, and treatments mediated by nanoparticle delivery which are designed to modify specific cell functions.